Socio-technical evolution of Decentralized Energy Systems: A critical review and implications for urban planning and policy - Adil, Ali M.; Ko, Yekang (Renewable & sustainable energy reviews, 2016)
The growth of Decentralized Energy Systems (DES) signals a new frontier in urban energy planning and design of local energy systems. As affordability of renewable energy technologies (RET) increases, cities and urban regions become the venues, not only for energy consumption but also for generation and distribution, which calls for systemic and paradigmatic change in local energy infrastructure. The decentralizing transitions of urban energy systems, particularly solar photovoltaic and thermal technologies, require a comprehensive assessment of their sociotechnical co-evolution – how technologies and social responses evolve together and how their co-evolution affects urban planning and energy policies. So far, urban planning literature has mainly focused on the impact of physical urban forms on efficiency of energy consumption, overlooking how the dynamics of new energy technologies and associated social responses affect local systems of energy infrastructure, the built environments and their residents. This paper provides an interdisciplinary review on the co-evolving technical and social dynamics of DES focusing on Distributed Generation (DG), MicroGrids (MG), and Smart MicroGrids (SMG), in order to draw insights for their integration in urban planning and policy, in particular reference to climate change mitigation and adaptation planning.